Examining Adolescence as a Sensitive Period for High-Fat, High-Sugar Diet Exposure: A Systematic Review of the Animal Literature - Murray, Susan; Chen, Eunice Y. (Frontiers in Neuroscience, 2019)
Animal studies suggest that poor nutrition (e.g., high-fat, high-sugar diets) may lead to impairments in cognitive functioning. Accumulating evidence suggests that the deleterious effects of these diets appear more pronounced in animals maintained on this diet early in life, consistent with the notion that the developing brain may be especially vulnerable to environmental insults. The current paper provides the first systematic review of studies comparing the effects of high-fat, high-sugar diet exposure during adolescence and adulthood on memory performance. The majority of studies (7/8) identified here report diet-induced memory problems when diet exposure occurred in adolescence. In contrast, such effects were not observed when diet exposure took place in adulthood. These findings lend support to the hypothesis that adolescence is a sensitive period during which palatable diets may contribute to negative neurocognitive effects. The current review explores putative mechanisms involved in diet-induced cognitive function and highlights promising areas for further research.